A Signal Processing Approach for the Recovery of the High-Q Resonance Profile for Dielectric Measurements. - Downing, Daniel. (2017)
Abstract: The Fabry-Perot open resonator is widely recognized as a powerful tool for the measurement of dielectric permittivity and loss tangent in low-loss materials at millimeter wave frequencies. The measurement technique that yields the most precise data with this instrument involves varying the length of the resonant cavity in steps as small as 10nm. Achieving length variations of this magnitude brings about many unique challenges that often lead to corrupted data and introduction of error into dielectric measurements. A novel signal processing technique has been developed to recover the assumed resonance profile and extract information needed to measure permittivity and loss tangent. Corrupted data was acquired using a 60GHz open resonator system on dielectric specimens that had previously been measured. The signal processing technique was applied to this data and produced measurements with similar accuracy as previously acquired uncorrupted data. This method, when applied to uncorrupted data, will likely further improve the precision of dielectric property measurements.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Electrical Engineering.; Advisor: Mohammed Afsar.; Committee: Douglas Preis, and Joshua Wilson.; Keyword: Electrical engineering.